Claims about medical malpractices resulting in maternal and perinatal mortality referred to iranian legal medicine organization during 2011-2012 - Ziba Taghizadeh; Maryam Pourbakhtiar; Masoud Ghadipasha; Kamran Soltani; Khadijeh Azimi (Wolters Kluwer Medknow Publications, 2017)
Background: Obstetricians, gynecologists, and midwives are the most common specialists of the medical sciences group against whom medical malpractices are claimed, many of which are avoidable and preventable. Therefore, the present study was conducted to investigate the causes of claims regarding medical malpractices resulting in maternal and perinatal mortality. Materials and Methods: A descriptive cross-sectional study was conducted and 7616 claims of medical malpractices in the field of obstetrics, gynecology, and midwifery that were referred from all 31 provinces to the central commission of legal medicine were studied during 2011-2012. Therefore, the present research is a national inclusive study covering all the provinces across Iran. To collect information from the transcript of medical malpractices cases, a researcher-made checklist was used, and the collected data were analyzed. Results: The results of the present study showed that among all the medical malpractice claims regarding pregnancy and childbirth (42.24%), the majority concerned perinatal death (71.82%) and maternal death (28.16%). Conclusions: Medical malpractice complaints are increasing; although, most of these claims are preventable. To achieve this aim, it is necessary for obstetricians, gynecologists, and midwives to try to reduce the complaints by paying more attention to the signs and symptoms of diseases, performing all the diagnostic and therapeutic measures according to the scientific criteria, and fully document patients' records. In addition, patients' acquaintance with the importance of measurements and examinations, before and during pregnancy care and even after childbirth is crucial.